A comparison of outcomes between a lumen-apposing metal stent with electrocautery-enhanced delivery system and a bi-flanged metal stent for drainage of walled-off pancreatic necrosis - Bekkali, Noor L. H.; Nayar, Manu K.; Leeds, John S.; Charnley, Richard M.; Huggett, Matthew T.; Oppong, Kofi W. (Endoscopy International Open, 2017)
Background and study aims Bi-flanged metal stents (BFMS) have shown promise in the drainage of walled-off pancreatic necrosis (WON), but their placement requires multiple steps and the use of other devices. More recently, a novel device consisting of a combined lumen-apposing metal stent (LAMS) and electrocautery-enhanced delivery system has been introduced. The aim of this study was to compare the placement and outcomes of the two devices.Patients and methods This was a retrospective review of consecutive patients undergoing endoscopic ultrasound-guided placement of BFMS or LAMS for drainage of symptomatic WON. Data from procedures between October 2012 and December 2016 were taken from a prospectively maintained database. We compared technical and clinical success, procedure time, costs, and composite end point of significant events (adverse events, stent migration, additional percutaneous drainage) between BFMS and LAMS.Results 72 consecutive patients underwent placement of BFMS (40 patients, 44 stents) or LAMS (32 patients, 33 stents). Technical success was 91 % for BFMS and 97 % for LAMS. Clinical success was 65 % vs. 78 %, respectively. Median in-room procedure time was significantly shorter in the LAMS group (45 minutes [range 30 – 80]) than in the BFMS group (62.5 minutes [range 35 – 135]; P < 0.001) and fewer direct endoscopic necrosectomies (DEN) were performed (median 1 [0 – 2.0] vs. 2 [0 – 3.7], respectively; P = 0.005). If only inpatients were considered (35 BFMS and 19 LAMS), there was no significant difference in DEN 2 (range 0 – 11) and 2 (range 0 – 8), respectively. The composite end point of 32 % vs. 24 % was not significantly different. Median procedural costs for all patients with successful stent placement for WON treatment was €4427 (range 1630 – 12 926) for BFMS vs. €3500 (range 2509 – 13 393) for LAMS (P = 0.10).Conclusion LAMS was superior to BFMS in terms of procedure time, with comparable adverse events, success, and costs.